A Functional oriT in the Ptw Plasmid of Burkholderia cenocepacia Can Be Recognized by the R388 Relaxase TrwC - Fernández-González, Esther; Bakioui, Sawsane; Gomes, Margarida C.; O'Callaghan, David; Vergunst, Annette C.; Sangari, Félix J.; Llosa, Matxalen (Frontiers in Molecular Biosciences, 2016)
Burkholderia cenocepacia is both a plant pathogen and the cause of serious opportunistic infections, particularly in cystic fibrosis patients. B. cenocepacia K56-2 harbors a native plasmid named Ptw for its involvement in the Plant Tissue Watersoaking phenotype. Ptw has also been reported to be important for survival in human cells. Interestingly, the presence of PtwC, a homologue of the conjugative relaxase TrwC of plasmid R388, suggests a possible function for Ptw in conjugative DNA transfer. The ptw region includes Type IV Secretion System genes related to those of the F-plasmid. However, genes in the adjacent region shared stronger homology with the R388 genes involved in conjugative DNA metabolism. This region included the putative relaxase ptwC, a putative coupling protein and accessory nicking protein, and a DNA segment with high number of inverted repeats and elevated AT content, suggesting a possible oriT. Although we were unable to detect conjugative transfer of the Ptw resident plasmid, we detected conjugal mobilization of a co-resident plasmid containing the ptw region homologous to R388, demonstrating the cloned ptw region contains an oriT. A similar plasmid lacking ptwC could not be mobilized, suggesting that the putative relaxase PtwC must act in cis on its oriT. Remarkably, we also detected mobilization of a plasmid containing the Ptw oriT by the R388 relaxase TrwC, yet we could not detect PtwC-mediated mobilization of an R388 oriT-containing plasmid. Our data unambiguously show that the Ptw plasmid harbors DNA transfer functions, and suggests the Ptw plasmid may play a dual role in horizontal DNA transfer and eukaryotic infection.